Impacts of Social Worker and Social Change on Mental Health - Rajanna G. (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
This article discusses the effects of social change on mental health and social worker role. It seems likely that no society can be utterly stable, despite reports of primitive societies or peasant communities which convey the impression of an unchanged and unchanging cultural history. The most critical and widespread source of social change in the contemporary world lies in the complex of technological and industrial advances. The consequences of the Industrial Revolution can be traced further in its implications for education, social legislation and childbearing practices. Even more remote effects on public health practices, on disease and on mental health remain the subjects of continuing study.